Assessment of knowledge and perception about silver diamine fluoride (SDF) for treating older adults among graduating dental students. Issue 11 (27th June 2020) - Dang, Connor; Comnick, Carissa L; Tabrizi, Maryam; Kaufman, Laura; Soto, Annetty; Smith, Becky M.; Ribeiro, Ana Paula Dias; Tobey, Tamara; Capin, Oriana Reis; Scully, Allison; Prince, David; Xie, Xian Jin; et al.
Abstract: Purpose/objectives: Silver diamine fluoride (SDF) is a promising therapy for arresting and preventing caries in difficult to treat, high‐risk populations, including institutionalized older adults. This study investigates the knowledge and perceptions about SDF of graduating dental students in multiple U.S. dental schools, as well as their willingness to use SDF in their practices. Methods: A survey was designed consisting of 21 total questions: 6 questions regarding students' demographic information and their SDF content exposure contextualization, 8 questions tailored to investigate 2 domains regarding students' knowledge about SDF (properties and indication), and 7 questions aiming to investigate 3 domains regarding students' perceptions about SDF (SDF usefulness, appropriateness of using SDF, and willingness to use SDF when in private practice). The survey was then distributed to graduating dental students at 7 U.S. dental schools. Results: A total of 386 surveys (response rate of 55%) was collected from 7 schools in the Spring of 2019. The median score resulting from the SDF content exposure questions was 3 (SD = 1.43) from a range of 0‐5. The median score from knowledge about SDF properties was 4 (SD = 1.18) from a range of 0 to 6. In the multivariate analysis, a linear model found that the covariates "SDF Usefulness", "SDF Appropriateness" and "SDF Patient Willingness to Use" were significantly associated with higher student willingness to use SDF (R 2  = 0.395). Conclusion: The results indicated that the graduating students have a positive perception of SDF regarding its usefulness and appropriateness. Graduating students appear inclined to utilize SDF upon entering private practice.